Adult ESL learners' experience in providing and receiving oral assessment feedback: a case study / Siti Aishah Taib - Taib, Siti Aishah (2014)
Recently there has been an influx of postgraduate students in order to improve the quality of teaching and learning in Malaysian higher education institutions. These postgraduate students, who are mostly adults, learn differently from the traditional students and bring their previous learning experience to the classroom. Adult learners initiate their own learning and assume the responsibility to complete their learning process. Should their performance fail to correspond to the prescribed learning goals, feedback is delivered to reduce the gap. However, it has been reported that feedback scored the lowest percentage of student satisfaction in 2011 National Student Survey. Despite their desire to receive more feedback from the instructors, studies show that students are unable to make use of the feedback. Meanwhile, peer feedback is also useful to help students reflect and improve their work. This study examines adult ESL learners' understanding of oral assessment feedback and their experience in providing and receiving oral assessment feedback. Observations, written interviews, and structured interviews are employed in order to obtain qualitative data to answer the research questions in this study. A group of adult learners and their lecturer are selected as participants in this study as they have to engage in teacher feedback and peer feedback processes in the classroom. The findings reveal that adult learners in this study understand the need to receive oral assessment feedback and are aware of the characteristics of effective feedback. However, adult learners appear to lack the ability to self-direct their learning when it concerns peer feedback process, due to four factors: (a) Attitude, (b) Knowledge, (c) Culture and Face Value, and (d) Feedback Preference. Nevertheless, the students are able to self-regulate their learning by acting upon the oral feedback they receive in spite of the negative feelings that they initially experience when they receive the oral feedback. Implications for practice include a discussion of the rationale for peer feedback process between the instructors and adult learners, a proper training on how to provide peer feedback and to effectively use the feedback for the adult learners, and a refinement of the peer feedback activity by conducting the activity in small groups, awarding marks for student participation in the activity, and shifting the role of the lecturer from being the sole feedback provider to the facilitator in the feedback process.